2017
DOI: 10.1186/s13287-017-0594-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mechanical stimulation on the reprogramming of somatic cells into human-induced pluripotent stem cells

Abstract: BackgroundMechanical stimuli play important roles in the proliferation and differentiation of adult stem cells. However, few studies on their effects on induced pluripotent stem cells (iPSCs) have been published.MethodsHuman dermal fibroblasts were seeded onto flexible membrane-bottom plates, and infected with retrovirus expressing the four reprogramming factors OCT4, SOX2, KLF, and c-MYC (OSKM). The cells were subjected to equiaxial stretching (3% or 8% for 2, 4, or 7 days) and seeded on feeder cells (STO). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…In addition, radio electric conveyed fields were sufficient to induce the neurogenic phenotype in PC12 cells, a model for dopaminergic neuron studies[76]. Finally, concerning cell reprogramming, several authors have shown that mechanical stimuli such as equiaxial stretching have an important role in reprogramming somatic cells into iPSCs, with the formation of a great number of iPSC colonies without using common viral mediated gene transduction[77]. These findings showed the prominence of physical stimuli in opening up new strategies for cell manipulation and regenerative medicine[78,79].…”
Section: Modulation Of Stem Cell Commitment By Physical Stimulimentioning
confidence: 99%
“…In addition, radio electric conveyed fields were sufficient to induce the neurogenic phenotype in PC12 cells, a model for dopaminergic neuron studies[76]. Finally, concerning cell reprogramming, several authors have shown that mechanical stimuli such as equiaxial stretching have an important role in reprogramming somatic cells into iPSCs, with the formation of a great number of iPSC colonies without using common viral mediated gene transduction[77]. These findings showed the prominence of physical stimuli in opening up new strategies for cell manipulation and regenerative medicine[78,79].…”
Section: Modulation Of Stem Cell Commitment By Physical Stimulimentioning
confidence: 99%
“…Reprogramming involves three sequential steps: initiation, stabilization, and maturation [106]. Indeed, molecular mediators, e.g., microRNA, or biophysical cues, e.g., nanotopography, can supplement or replace some of the classical reprogramming factors commonly used to enhance reprogramming efficiency [107113].…”
Section: Integrins and Ipscmentioning
confidence: 99%
“…Mechanical stimulation has been demonstrated to regulate FA assembly, modulating the downstream pathways affecting cardiomyogenesis [246249]. Based on this assumption, several methods have been described for the application of controlled mechanical stimulation (i.e., temporal, spatial, and amplitude), some of them aiming to verify the positive impact of integrin-mediated adhesion pathways on iPSC reprogramming [113] and differentiation [250, 251]. Although far from being exhaustively described, the pathways seem to be regulated by the change in FA density and local conformation [252], followed by impacting cytoskeleton rearrangement [56], finally regulating cardiomyocyte maturity, e.g., cell-cell contact, sarcomeric structure, and electrical activity.…”
Section: Integrin Relevance In Ipsc-derived Cells: In Vitro Biomimmentioning
confidence: 99%
“…However, in other studies, mechanical strain reduced the expression of pluripotency transcription factors and signaling pathways related to pluripotency in iPSCs 23 . Mechanical stretch also enhanced the reprograming of cells treated with retrovirus-delivered pluripotency transcription factors without altering the efficiency of viral transduction 24 . Other studies have linked alterations in pluripotency to changes in cell shape or substrate stiffness 25 27 .…”
Section: Introductionmentioning
confidence: 99%